+0  
 
0
49
2
avatar

0=x^4+5x^3-15x^2-5x+14

 

Anyone who can help me solve this? 

Guest Oct 21, 2017

Best Answer 

 #2
avatar+78577 
+1

x^4+5x^3-15x^2-5x+14  = 0       

 

Write -15x^2  as   -14x^2  - x^2

 

x^4+5x^3-14x^2 - x^2 -5x+14 = 0

 

x^2(x^2+ 5x - 14) - 1(x^2 + 5x - 14) = 0

 

(x^2 - 1) ( x^2 + 5x - 14) = 0

 

(x + 1) (x - 1) (x + 7) ( x - 2)  = 0

 

Set each factor to 0  and solve for x  and we get that x = -1, 1, - 7 or 2

 

 

cool cool cool

CPhill  Oct 21, 2017
Sort: 

2+0 Answers

 #1
avatar+26328 
0

This factorises as:

 

(x - 1)(x + 1)(x - 2)(x + 7) = 0

 

I'm sure you can take it from there!

Alan  Oct 21, 2017
 #2
avatar+78577 
+1
Best Answer

x^4+5x^3-15x^2-5x+14  = 0       

 

Write -15x^2  as   -14x^2  - x^2

 

x^4+5x^3-14x^2 - x^2 -5x+14 = 0

 

x^2(x^2+ 5x - 14) - 1(x^2 + 5x - 14) = 0

 

(x^2 - 1) ( x^2 + 5x - 14) = 0

 

(x + 1) (x - 1) (x + 7) ( x - 2)  = 0

 

Set each factor to 0  and solve for x  and we get that x = -1, 1, - 7 or 2

 

 

cool cool cool

CPhill  Oct 21, 2017

14 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details